2009
DOI: 10.1186/1471-2466-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected and extensive transmission of a drug-susceptible Mycobacterium tuberculosisstrain

Abstract: BackgroundA large and unsuspected tuberculosis outbreak involving 18.7% of the total of the tuberculosis cases studied, was detected in a population-based molecular epidemiological study performed in Zaragoza (Spain) from 2001 to 2004.MethodsThe Mycobacterium tuberculosis drug-susceptible strain, named MTZ strain, was genetically characterized by IS6110-RFLP, Spoligotyping and by MIRU-VNTR typing and the genetic patterns obtained were compared with those included in international databases. The characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…A large unsuspected TB outbreak involving 85 patients in Zaragoza, Spain, in 2001 to 2004 was attributed to the M. tuberculosis Zaragoza strain (35). The lack of the TbD1 region described here confirms that Zaragoza is a modern strain, in agreement with our previous work showing that the strain belongs to principal genetic group 3 (PGG-3) (35).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A large unsuspected TB outbreak involving 85 patients in Zaragoza, Spain, in 2001 to 2004 was attributed to the M. tuberculosis Zaragoza strain (35). The lack of the TbD1 region described here confirms that Zaragoza is a modern strain, in agreement with our previous work showing that the strain belongs to principal genetic group 3 (PGG-3) (35).…”
Section: Discussionsupporting
confidence: 81%
“…The lack of the TbD1 region described here confirms that Zaragoza is a modern strain, in agreement with our previous work showing that the strain belongs to principal genetic group 3 (PGG-3) (35). Other authors found that isolates belong- a Results of the analysis to detect the specificity of the IS6110 localization in 100 different clinical isolates are shown.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, this insertion is exclusive to the Beijing family of M. tuberculosis isolates and has led to the development of a method for screening M. tuberculosis strains (using either purified DNA or directly on respiratory samples) and reliably identifying those belonging to the Beijing family of strains. (12), and 13 that were Mycobacterium africanum (Table 1). Overall, this collection included samples that were representative of most of the M. tuberculosis genetic lineages that have been described (13).…”
mentioning
confidence: 99%
“…described Madrid 1 and Madrid 2 spoligopatterns with their corresponding MIT as probable specific clonal complexes in Spain [ 31 ]. Lopez Calleja et al described a strain, MTZ , causing a large cluster (85 isolates) in Zaragoza, which is also represented (MIT157) in our population [ 30 ]. Another significant finding in our phylogeoraphic structure is that we shared the majority of the clustered patterns with Belgium and Great Britain.…”
Section: Discussionmentioning
confidence: 99%